Surface-enhanced Raman Scattering Detection of Triazophos Based on Fe3O4@MIL-100(Fe)@Ag NPs - YANG Nengjing, ZHU Haofan, WEI Qingyi, SUN Da-wen, PU Hongbin (Shipin Kexue, 2023)
A core-shell-satellite nanostructure surface-enhanced Raman scattering (SERS) substrate based on magnetic nanoparticles, metal-organic frameworks (MOFs) and gold nanoparticles (Ag NPs) was established and applied in the simple, rapid and sensitive detection of the organophosphorus pesticide triazophos in agricultural products. MIL-100(Fe)-coated Fe3O4 was prepared by low-temperature cyclic self-assembly method, and Ag NPs were in-situ grown on the surface of MIL-100(Fe)-coated Fe3O4 by silver mirror cycling. The SERS sensing of triazophos residues in apples was carried out. The logarithmic value (Y) of the characteristic peak intensity of triazophos was linearly related to the logarithmic value (X) of its concentration in the range of 0.05–10 mg/L, which was described by the following equation: Y = 0.573 8X + 2.804 (R2 = 0.980). The limit of detection (LOD) was as low as 11.9 mg/L. The recoveries of the developed method ranged from 90.07% to 103.27% at spiked concentrations of 2, 5, and 10 mg/L. Therefore, the prepared SERS substrate has great potential for application in the detection of pesticide residues in foods.